STRONGYLOIDES STERCORALIS AND THE ESTRONGILOIDÍASE (CIPEEX, 2025)
These abstract aims to explore the parasite-host relationship of Strongyloides stercoralis. It is a nematode helminth with a filiform appearance that causes strongyloidiasis, an intestinal parasitic infection. This parasitosis is often underdiagnosed, especially in tropical and subtropical areas, and is asymptomatic in most cases. The parasite can reproduce both in the host and in the soil or manure, being characterized as a geohelminth. It has a monoxenic biological cycle, and dogs can also be hosts of this helminth. Humans can be infected only by parthenogenetic females, with a genetic load of 3n. In the environment, rhabditoid larvae can develop into infective filariform larvae, also called L3, promoting the direct cycle. However, the eggs of the parthenogenetic female can generate free-living male and female after development in the soil of the immature larvae, in the indirect cycle. Thus, the male and female in the soil can also generate 3n larvae. Transmission occurs by active penetration of larvae, making the habit of walking barefoot an important factor associated with cases of parasitosis. However, strongyloidiasis is one of the intestinal parasitoses that is difficult to diagnose, in addition to being chronic and asymptomatic, it can cause gastrointestinal, respiratory and skin symptoms. In intestinal infection, epigastric pain, like gastritis, is often reported. Diarrhea, pruritus, nausea, vomiting, weight loss, and weakness may also occur. The diagnosis of strongyloidiasis is made based on the detection of larvae in feces, sputum or duodenal fluid. In the laboratory, the general method can be performed in the feces, and if the sample is fresh, the hydrothermotropism of the larvae, a specific method for S. stercoralis. However, strongyloidiasis is difficult to diagnose as the low parasite load and larval production is irregular in most patients. Its medical importance stands out in cases of immunosuppression, when intense parasite multiplication can occur with extraintestinal migration of the parasite.  Keywords: Immunosuppression; HIV; parasitosis.
Keywords: immunosuppression; hiv; parasitosis